Melatih Kepercayaan Diri Siswa dalam Menyatakan Tanggapan dan Saran Sederhana melalui Penguatan Pujian pada Pembelajaran Bahasa Indonesia - Mariam Magdalena (Jurnal KIBASP (Kajian Bahasa, Sastra dan Pengajaran), 2018)
The purpose of this paper describes the activities and models of Indonesian language learning in SD Negeri 133 Seluma on the material provide simple responses and suggestions. The research method is literature study by using knowledge and teaching experience in class IV SD Negeri 133 Seluma. Where this research illustrates from the observations that exist in the Seluma state primary schools. The results show that gift giving and praise are rewards or rewards for good behavior by children. In the poses of learning in schools many factors that affect the process and learning outcomes are internal and external factors. In the learning of Indonesian in elementary school class IV there is the material meyampaikan opinion rebuttal or suggestion. From the observation of the researcher shows that students are often shy (not confident) in expressing opinions or rebuttal. By providing reinforcement in the form of rewards through the form of praise will train the child to active learning and students are able to express opinions or arguments with an effective language. Based on the experience of the authors in providing learning in class IV, students are very excited if the learning is packed with as attractive as possible. Researchers packed fun learning by awarding rewards through direct speech or verbal or non verbal reinforcement in fourth grade SD Negeri 133 Seluma. Keywords: Response, Reinforcement, Praise, Learning.